Pembinaan Prestasi Cabang Olahraga Bola Voli di Klub DPU Pati Tahun 2020 (Universitas Negeri Semarang, 2021)
Management at DPU Pati club is still not optimal due to the lack of human resourcesof the management, the lack of complete facilities and infrastructure due to the lackof budget funds, and the lack of training hours at the club so that it is still notoptimal in planning training programs. The purpose of this study was to determinethe mass, nursery, and achievements in coaching the achievements of volleyball inthe DPU Pati club in 2020. This type of qualitative research uses descriptivemethods. Data collection techniques using interviews, documentation, andobservation. The resource persons are 9 people consisting of 1 administrator, 2coaches, and 6 athletes. Checking the validity of the data used triangulation of dataand sources. The data analysis technique used includes data reduction, datapresentation, and verification. The results of the research obtained informationthat (1) the implementation of mass activities has been going well, because there isa strategy of practice which is carried out directly through championships once ayear and friendly matches, (2) the nursery has been going well, because there is atiered and open age grouping, (3) the achievement is quite good, because everytime he participates in the championship, DPU Pati Club always brings home thechampion, even though he has not been able to defend the first winner.